If the equations ax^2+bx+c=0 and x^3+3x^2+3x+2=0 have two common solutions then show a=b=c.
first equation will be the factor of second.
taking out common from first equation.
how to show a=b=c??
please provide hints.
If the equations ax^2+bx+c=0 and x^3+3x^2+3x+2=0 have two common solutions then show a=b=c.
first equation will be the factor of second.
taking out common from first equation.
how to show a=b=c??
please provide hints.
can we solve by the following formulas
for quadratic eqs.
α+ß =-b/a
αß= c/a
for cubic equations
(Γ=gamma)
α+ß+Γ=-b/a
(αß)+(ßΓ)+(αΓ)=c/a
αßΓ=-d/a
i am trying to solve by this method but i hung up! in between?